2013
DOI: 10.1007/s12185-013-1321-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of Th1 and Th2 cytokines with transient inflammatory reaction during lenalidomide plus dexamethasone therapy in multiple myeloma

Abstract: Transient inflammatory reactions have been reported in a subpopulation of patients with multiple myeloma (MM) during lenalidomide (Len) plus dexamethasone (DEX) therapy. Here, we examined serum levels of Th1 (IL-2 and IFN-γ) and Th2 cytokines (IL-6 and TNF-α) in nine refractory or relapsed MM patients treated with Len plus low-dose DEX. Six patients showed elevation of C-reactive protein (CRP) after the initiation of therapy. In these patients, IFN-γ and IL-6 were also elevated in two and three patients, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…Richter et al [12] reported that lenalidomide induces eosinophilia through the activation of NK/T cells. In addition, there are reports that human eosinophils produce IL-6 [13] and that many patients with myeloma show increase of the serum IL-6 during treatment with lenalidomide [14]. However, there is also a report of the serum ILb Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Richter et al [12] reported that lenalidomide induces eosinophilia through the activation of NK/T cells. In addition, there are reports that human eosinophils produce IL-6 [13] and that many patients with myeloma show increase of the serum IL-6 during treatment with lenalidomide [14]. However, there is also a report of the serum ILb Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In general, inflammation is frequently observed in cancer patients receiving treatment modalities with various modes of action. Transient inflammatory reactions have been reported in subgroup of patients with MM during lenalidomide plus dexamethasone therapy [11]. The inflammatory response is characterized by coordinate activation of various signalling pathways including NF-κB in resident tissues [12].…”
mentioning
confidence: 99%
“…Despite pro-inflammatory cytokine deregulation being postulated as a mechanism of lenalidomide-induced hypothyroidism, pre- and post-treatment serum inflammatory cytokine levels following lenalidomide administration have only been published in one small case series and have not been assessed in relation to the development of hypothyroidism. In a group of six patients with MM and a significant elevation (over 1 mg/dL increase) in C-reactive protein (CRP) after lenalidomide treatment, Harada et al found no significant increase in serum tumor necrosis factor alpha (TNF-α), interferon gamma (IFN- γ ), interleukin-2 (IL-2), or interleukin-6 (IL-6) after therapy[7]…”
Section: Discussionmentioning
confidence: 99%